TINGENE SLADRER: En ganske uvidenskabelig tur gennem danskernes trang til kollektiv individualisme - Hansen, Jørn Duus (Tidsskriftet Antropologi, 2001)
In our modern life we are surrounded by thousands of objects. In between them they form innumerable and complex patterns by which one person distinguishes himself or herself from an other with respect to objects, food, clothes, the home, cars. This is how separate ethnies, territories or clubs are formed, with more or less identical collections of objects. It seems as if we wish to be in a region (“them and us”) and at the same time be independent beings within the region (“you and me”). We all are something owing to our objects. Or is it the other way around? Are our objects something owing to the other objects they are combined with? We might have chosen them, but, nevertheless, they seem to chose each other! And might it not be that the objects can change their connotation, simply by being moved into another region or territory ? It is particular modern things which distinguish the region of modern life from the region of traditional, folk life. There are objects which distinguish one modern space from another. I am speaking about faint nuances, but they are obvious to the user and the viewer. Social individualism is far more widespread than authentic originality individualism. Among the younger members of the population, an ironic sense of originality is emerging, where very popular, folk things suddenly are considered original by being combined in new and very unfolklike fashions. Is this to be understood as a protest against the canons of elitist judgements? Or is it simply to be understood as a desire to rediscover the traditional folk ways?